ChemInform Abstract: Fluorescent Monomers as Building Blocks for Dye Labeled Polymers: Synthesis and Application in Energy Conversion, Biolabeling and Sensors. Issue 36 (15th August 2013) - Breul, Alexander M.; Hager, Martin D.; Schubert, Ulrich S.
Abstract Review: 271 refs.